HUBUNGAN KEPUASAN KERJA DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA KARYAWAN PERUM BULOG KANTOR SUB DIVRE VI WILAYAH PEKALONGAN - Ardini Fahmiprimanti; Siswi Jayanti; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Background: Low back pain is non traumatic musculoskeletal disorders. Cases of low back pain occurs in many workplaces and causes various impacts, ranging from feel uncomfortable at work, working days lost until turnover. The causes of low back pain can be derived from individual factors and workplace factors, some of them are job satisfaction and ages. The purpose of this study is analyzing the relationship between job satisfaction and ages with complaints about low back pain employees of Perum Bulog Kantor Sub Divre VI Wilayah Pekalongan.Method: This study was a survey research with cross sectional approach. Dependent variable is complaints about low back pain and independent variable are job satisfaction and ages. Sampling method of this study is purposive sampling. Spearman’s Rank Correlation were employed as analysis tools. The population in this study are employees of Perum Bulog Kantor Sub Divre VI Wilayah Pekalongan which totaled 26 people. Respondents were 22 people.Result: The results of research known that there was significant relationship between complaints about low back pain with the job satisfaction (p = 0,008) and there was significant relationship between complaints about low back pain with ages (p = 0,008). For employees, suggested to do exercises stretching routinely with some alternatives movement and increase social relationships between coworkers.